Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208322
|View full text |Cite
|
Sign up to set email alerts
|

Balancing exertion experiences

Abstract: Exercising with others, such as jogging in pairs, can be socially engaging. However, if exercise partners have different fitness levels then the activity can be too strenuous for one and not challenging enough for the other, compromising engagement and health benefits. Our system, Jogging over a Distance, uses heart rate data and spatialized sound to create an equitable, balanced experience between joggers of different fitness levels who are geographically distributed. We extend this prior work by analyzing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 24 publications
1
84
0
Order By: Relevance
“…One of the biggest challenges in this domain is in designing mechanics that don't consistently give advantage to bigger and stronger players. Video game designers often create balance in multiplayer games through penalizing strong players and boosting weak players [4], and in non-contact exertion games by modulating effort required based on player fitness [20]. That strategy seems less feasible in brutal games, where there is no obvious way to handicap players.…”
Section: Design For Balancementioning
confidence: 99%
“…One of the biggest challenges in this domain is in designing mechanics that don't consistently give advantage to bigger and stronger players. Video game designers often create balance in multiplayer games through penalizing strong players and boosting weak players [4], and in non-contact exertion games by modulating effort required based on player fitness [20]. That strategy seems less feasible in brutal games, where there is no obvious way to handicap players.…”
Section: Design For Balancementioning
confidence: 99%
“…Different approaches for balancing exertion games have emerged in literature: The game Life is a Village [23] implements asymmetric player roles (cycling on a recumbent bike and using the Nintendo Wii Remote for gestural input), whereas Heart Burn [21] uses difference from target heart rates to balance for people with difference fitness levels. Likewise, Mueller et al [15] demonstrated that heart rate balancing contributes to player experience in a remote jogging application, because it allows players to focus on their own fitness levels while still engaging with another person.…”
Section: Balancing Multiplayer Experiencesmentioning
confidence: 99%
“…Smart solutions that balance based on the players' effort seem to be promising for allowing people with different physical skills play together [169,240]. Properly functioning adaptive (balancing) systems are often an ideological and unrealistic dream of the starting game designer [226].…”
Section: Adaptive Balancing and Steering Interactionsmentioning
confidence: 99%